2021
DOI: 10.1007/s00068-021-01657-5
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a wearable-controlled serious game and goniometer for telemonitoring of wrist fracture rehabilitation

Abstract: Purpose To determine the validity of wrist range of motion (ROM) measurements by the wearable-controlled ReValidate! wrist-rehabilitation game, which simultaneously acts as a digital goniometer. Furthermore, to establish the reliability of the game by contrasting ROM measurements to those found by medical experts using a universal goniometer. Methods As the universal goniometer is considered the reference standard, inter-rater reliability between surgeons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Based on eligibility criteria, a total of 28 studies were included in this review. 28–56 Figure 1 illustrates the PRISMA flow chart describing the article selection process. The KAPPA statistics for agreement between the two reviewers were between moderate and substantial at 0.47 and 0.66 for the title and abstract screen and the full-length text screening, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on eligibility criteria, a total of 28 studies were included in this review. 28–56 Figure 1 illustrates the PRISMA flow chart describing the article selection process. The KAPPA statistics for agreement between the two reviewers were between moderate and substantial at 0.47 and 0.66 for the title and abstract screen and the full-length text screening, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…When categorizing studies based on whether the device used was high or low technology, we found that most studies utilized low technological telerehabilitation solutions (n = 23). [28][29][30][31][32][33][34][35][36][38][39][40][41][42][43]45,47,[49][50][51][52][54][55][56]…”
Section: Characteristics Of Telerehabilitation Technologiesmentioning
confidence: 99%
“…Specific engaging gamification mechanics include use of specific goals, achievements, feedback on progress and levels. Whether these effects will help overcome loss of interest is still not established, but it is generally believed that gamification principles have the power to increase user engagement, raise the quality of health behaviours (Alahäivälä and Oinas-Kukkonen, 2016), and provide an easy way of delivering direct feedback and improving supervision in exercise programmes (Meijer et al., 2018, 2022).…”
Section: Application Of Available and Emerging Technologiesmentioning
confidence: 99%
“…By use of image-based self-assessments, data on everyday pain and disability can be characterized while at the same time enhancing patient self-management and adherence to treatment protocols (Selter et al., 2018). Gamification principles (such as adding game mechanics via an App into non-game environments) can be added to the mobile applications as a further adjunct to improve patient motivation and make rehabilitation more enjoyable (Meijer et al., 2022; Xu et al., 2022). The basic idea is to draw on the motivational potential of (video) games and to motivate users to use the App for a sustained period.…”
Section: Application Of Available and Emerging Technologiesmentioning
confidence: 99%